SYNTHESIS OF NANOSIZED CuO-CeO2 MIXED OXIDE BY CITRATE SOL-GEL METHOD - Huong Hue, Hoang Thi; Bang, Nguyen Dinh (Vietnam Journal of Chemistry, 2012)
Nano-particles of CuO-CeO2 with the average particle size (10 - 40 nm) and surface area (45.3 m2/g) was obtained from a mixed solution of Ce(NO3)3, Cu(NO3)2, citric acid by the citrate sol-gel method as precursors. The characteristics of CuO-CeO2 mixed oxide were examined by means of X-Ray diffraction (XRD), H2-temperature-programmed reduction (H2-TPR) and the nitrogen adsorption and desorption (BET), transmission electron microscopy (TEM). The results indicated that there are CuO species in the CuO-CeO2 mixed oxide: the Cu2+ mostly exists in CuxCe1-xO2-d solid solution, the left in the finely dispersed CuO species on the surface of CeO2 and the bulk CuO. The calculating results from Powder Cell 2.4 software showed that, when CuO-CeO2 mixed oxide was formed, the cell parameter values of CeO2 was smaller than that of pure CeO2, indicating that some Cu2+ entered the CeO2 lattice.